Metal to insulator transition for conducting polymers in plasmonic nanogaps - Yuling Xiong; Rohit Chikkaraddy; Charlie Readman; Shu Hu; Kunli Xiong; Jialong Peng; Qianqi Lin; Jeremy J. Baumberg (Light: Science & Applications, 2024)
Abstract Conjugated polymers are promising material candidates for many future applications in flexible displays, organic circuits, and sensors. Their performance is strongly affected by their structural conformation including both electrical and optical anisotropy. Particularly for thin layers or close to crucial interfaces, there are few methods to track their organization and functional behaviors. Here we present a platform based on plasmonic nanogaps that can assess the chemical structure and orientation of conjugated polymers down to sub-10 nm thickness using light. We focus on a representative conjugated polymer, poly(3,4-ethylenedioxythiophene) (PEDOT), of varying thickness (2-20 nm) while it undergoes redox in situ. This allows dynamic switching of the plasmonic gap spacer through a metal-insulator transition. Both dark-field (DF) and surface-enhanced Raman scattering (SERS) spectra track the optical anisotropy and orientation of polymer chains close to a metallic interface. Moreover, we demonstrate how this influences both optical and redox switching for nanothick PEDOT devices.